135 CMT with renal impairment: consider a dip. Issue 6 (27th May 2022) - Doherty, Carolynne; Blake, Julian; Skorupinska, Mariola; Shah, Sachit; Laura, Matilde; Reilly, Mary
Abstract : Background: We describe two patients from our neuropathy cohort who have CMT with slowed conduc- tion velocities (CV) and renal involvement and discuss the importance of urine dipstick testing in those without a genetic diagnosis. Cases: A 19-year-old had deterioration in his running aged 3, required foot surgery aged 10 and scoliosis surgery aged 15. Distal atrophy and weakness with large fibre sensory impairment was evident. At age 12, neurophysiology demonstrated absent SAPs, reduced CMAPs and MCVs of 10–18m/s. Urine dipstick showed proteinuria. Whole genome sequencing demonstrated a previously described p.Cys104Tyr INF-2 mutation.(1) Another patient required renal transplantation attributed to scarlet fever in her 20's. CMT was diagnosed age 11, again requiring foot surgery and scoliosis management. A NGS panel identified the previously described p.Val102Asp INF-2 mutation.(2) Discussion: Mutations in INF-2 are associated with dominant nephrotic syndromes including Focal Segmental Glomerulosclerosis of varying severity, including needing renal transplants. CMT, typically inter- mediate, is not always present, with latest described onset age 28, and may precede renal involvement. As identification and management of nephrotic syndrome is crucial, we advocate urine dipstick testing in CMT patients who do not yet have a genetic diagnosis, particularly in the presence of slowed MCV. 1) Bacquet J, et al.Molecular diagnosis of inherited peripheral neuropathies by targeted next-generation sequencing:Molecular spectrum delineation. BMJ Open.2018;8(10):1–14. 2) Challis RC, et al. Thrombotic microangiopathy in inverted formin 2-mediated renal disease. JAmSocNephrol.2017;28(4):1084–91. carolynnedoherty@doctors.org.uk|NIHR Bursary